Technique of Aortic Root Reconstruction Using a New Model of Dacron Graft with Prefabricated Coronary Branches. Issue 6 (November 2014) - Calcaterra, Domenico; Farivar, Robert S.; Parekh, Kalpaj R.; Bashir, Mohammad; Karam, Karam; Turek, Joseph W.
Aortic root reconstruction is a demanding surgical procedure still associated with a significant morbidity. Arguably, the most demanding aspect of the operation is reestablishing continuity between the prosthetic graft replacing the aortic root and the coronary arteries. With the objective of simplifying the possible challenges of coronary reimplantation, we designed a new model of aortic root graft with prefabricated coronary branches. We used this technique in 8 patients (6 males, 2 females; mean age, 54 years). There were 6 modified Bentall procedures and 2 valve-sparing root replacements with the "reimplantation" technique. There was no mortality or morbidity related to the use of this new prosthetic graft. Our purpose was to report in detail the technique of aortic root reconstruction using this new graft with prefabricated coronary branches. The use of this graft may simplify the procedure and offer a valuable tool for aortic root reconstruction in cases where the reimplantation of the coronary buttons may represent a technical challenge.